Human language technology challenges for computer science and linguistics : 6th Language and Technology Conference, LTC 2013, Poznań, Poland, December 7-9, 2013, Revised selected papers /: 6th Language and Technology Conference, LTC 2013, Poznań, Poland, December 7-9, 2013, Revised selected papers. (2016) - Unknown
No abstract available